Accumulation of organic-rich sediments associated with Aptian–Albian oceanic anoxic events in central-eastern Mexico. (October 2022) - Gutiérrez-Puente, Nicté A.; Barragán, Ricardo; Núñez-Useche, Fernando; Enciso-Cárdenas, Juan Josué; Martínez-Yáñez, Mario; Camacho-Ortegón, Luis Fernando
Abstract: Oceanographic and climate conditions during the early Aptian OAE 1a and the late Aptian–early Albian OAE 1b are reported from an organic-rich succession deposited in the central portion of the Mexican Interior Basin, based on the analysis and integration of geochemical data (δ 13 Ccarb, total organic and inorganic carbon contents, Rock-Eval parameters and major and trace elements concentrations). The carbon isotope record of the studied section displays trends that correlate with segments C2 to C13. The OAE 1a interval is clearly isotopically defined (segments C3–C6) and includes sediments moderately enriched in organic matter. Although the OAE 1b sub-events are not expressed in the isotope record, the Jacob, Kilian and Paquier events may correspond to distinctive organic-rich levels occurring through C10–C12 segments. Evidence indicates that sediments enriched in organic matter through the section were accumulated under oxygen-depleted and high nutrient conditions. Anoxic-eutrophic conditions induced by a high input of continental-derived nutrients (including biolimiting Fe and P) associated to intense chemical weathering under warm and humid conditions took place during the deposition of the Selli and Paquier levels. Enhanced P recycling and regional upwelling reinforced eutrophic conditions during OAE 1a. Highlights: Organic-rich sediments deposited during OAE 1a and OAE 1b. Anoxic-eutrophic conditions favored the formation of the Selli and Paquier levels. Warm and humid conditions led to an enhanced supply of nutrients to the basin. P recycling and upwelling reinforced eutrophication.